Music as a Research Object of Cultural Anthropology by George Herzog - M. P. Zamotin (Дискурс, 2020)
Introduction. Being a universal art form, music in cultural anthropology was understood as a key element of human life throughout the world, represented in a variety of genres, ways of processing sounds, creating harmony, creating song folklore that reflects all aspects of human life. Ethnomusicology, as a unique research field, combined an interest in music both in the form of art and in its sociocultural context. This paper is devoted to the research activity of J. Herzog, thanks to whose efforts the study of folk “primitive” music went beyond musicology and diversified the subject area of cultural anthropology. The relevance of this study is due to the fact that the name of Herzog and his views are not well known in Russia, except for specialized areas of ethnographic and musicological nature.Methodology and sources. As a methodological basis, a comparative historical methodology and a structural-functional method are used to study scientific texts and subsequent processing and generalization of the theoretical constructs of G. Herzog. A biographical method wasused as well to understand the context of time and reveal the scientist’s intellectual genesis.Results and discussion. One of the pioneers in the field of ethnomusicology, G. Herzog used transcription methods and sound analysis in combination with theories and methods of the Boas school, which included the concept of diffusion and the method of field work. Interdisciplinary cooperation in the study of primitive and folk music was an important step for the researcher, since this approach brought the study of folk music to a new level of conceptualization. Herzog was interested in explaining and classifying primitive music and songs in terms of the “root” terms and concepts used by his informants.Conclusion. The interdisciplinary approach in the use of methods for fixing and interpreting musical material in ethnomusicological research by G. Herzog made it possible to overcome the evolutionary linear methodology of studying the musical culture of primitive peoples and draw attention to the context of performance and performers.